A highly selective and sensitive "off-on" fluorescent probe for the detection of nerve agent mimic DCNP in solution and vapor phase. (February 2021) - Xu, Hui; Zhang, Han; Wang, Chengyi; Chen, Kang; Liu, Guohua; Tan, Chunxia; Cheng, Tanyu
Abstract: Chemical warfare agents (CWAs) are the most feared and unpredictable terrorist weapon that threaten global security. For the issue of human security, it is highly demanded to establish rapid and reliable methods for the detection of CWAs. In this work, a hemicyanine-based colorimetric and off-on fluorescent dual-modal probe for the detection of a nerve agent mimic diethyl cyanophosphonate (DCNP) has been developed. The probe exhibits fast response (<3 min), high selectivity, and excellent sensitivity with a low limit of detection (4.5 nM). More importantly, test strips loaded with the probe can sense DCNP vapor in low concentration and distinguish DCNP vapor from other nerve agent mimics by both naked eyes and fluorescence. Graphical abstract: Image 1 Highlights: An ultrasensitive OFF-ON fluorescent probe for DCNP was developed. The probe exhibited a fast fluorescence response to DCNP within 180 s with a low detection limit of 4.5 nM. The probe displayed colorimetric and fluorescent dual-responses for DCNP. The filter paper with the probe can sensitively and selectively detect DCNP vapor.